Status, diversity and potential of indigenous tropical tuber vegetables - Chauhan, V B S; Pati, Kalidas; Bansode, V V; Nedunchezhiyan, M (Indian Horticulture, 2020)
Several economically desirable important genetic stocks identified from the germplasm are under advanced stages of evaluation. Taro germplasm collection, characterization and evaluation under different agro-ecology plays great role for variability identification, conservation of desirable genotypes and utilization in crop improvement through breeding.